“Late” Withdrawal Syndrome after Carbamazepine In Utero Exposure in a CYP2C9 Slow Metabolizer Newborn - Passia, Evangelia; Rock, Nathalie; Pfister, Riccardo E.; Ing Lorenzini, Kuntheavy R.; Desmeules, Jules; Samer, Caroline F. (Frontiers in Pharmacology, 2017)
We report a case of carbamazepine withdrawal syndrome following in utero exposure to carbamazepine related to a pharmacogenetic predisposition factor. The infant was born at 37 1/7 weeks’ gestation by cesarean section to a mother treated for epilepsy with carbamazepine. One hour and thirty minutes after birth, the infant presented a respiratory distress with severe oxygen desaturation requiring intubation five hours after birth. On the third day of life the infant developed clinical signs of a withdrawal syndrome which resolved progressively after 16 days and symptomatic treatment. The infant genotype analysis showed two low activity CYP2C9 allelic variants (*2/*3) predicting a CYP2C9 slow metabolizer phenotype which could explain reduced carbamazepine elimination and a late and long-lasting withdrawal symptoms observed 3 days after birth. The association of a withdrawal syndrome with carbamazepine exposure has not been previously reported and pharmacogenetic tests might therefore be useful in identifying patients at risk.